Analysis of the characteristics of geography study tour program development in China - Dinghui Liu; Wentao Yang; Xinrui Zhan; Chuanci Feng (PLoS ONE, 2025)
Using 730 winning entries in the 2023 “Kyushu Cup” National Study Tour Program Design Competition as examples, this article analyzes characteristics of geography study tour program development in China via GIS and SPSS software. The study results show that the development of geography study tour programs in China is unbalanced in terms of spatial distribution, course content, main body of design, and field trip scope. The following manifestations were observed: first, there are large spatial and administrative differences in the development of Chinese geography study tour programs; second, although geography is a comprehensive discipline that emphasizes the holistic nature of regional studies, the proportion of comprehensive regional study tours is relatively low; third, colleges and universities are the primary developers of geography study tour programs, followed by secondary schools; and finally, the development of Chinese geography study tour programs is dominated by local study tours, which are mainly based on vernacular geography. This study provides new insight into the spatial and administrative disparities in geography study tour programs, highlights the lack of comprehensive regional study tours, and offers practical recommendations for promoting a more balanced and interdisciplinary approach to geography education in China.